Mental well-being of medical students: Do lifestyles and physical activity make any difference? - Cijan, Ana; Cvetković, Jelena; Mandić-Rajčević, Stefan; Stevanović, Aleksandar; Stamenković, Željka; Todorović, Jovana (Medical Research, 2025)
Introduction: Lifestyle, which includes dietary habits, physical activity, smoking and alcohol consumption, among other factors, affects the health of the individual and the population as a whole. Regular physical and healthy lifestyle also reduce the burden of chronic disease. Medical students often have a suboptimal activity level and unhealthy lifestyle habits, affecting their well-being and future medical practice. The aim of this research was to examine the frequency of insufficient physical activity and lifestyle factors associated with physical activity among fifth-year medical students at the Faculty of Medicine, University of Belgrade, as well as their association with the physical and mental health of students. Methods: A cross-sectional study was conducted among fifth-year medical students at the Faculty of Medicine, University of Belgrade during the Social medicine course in November 2023. An anonymous questionnaire was used to assess physical activity, lifestyle characteristics, and symptoms of depression and anxiety. The study included 432 students, achieving a 90.4% participation rate. Participants were categorized into groups with sufficient and insufficient physical activity levels based on energy expenditure. Results: Altogether, 379 students (92%) were in the group with sufficient physical activity, while 33 (8.0%) were in the group with insufficient physical activity. Conclusion: Physical inactivity was significantly associated with female gender, lower BMI (OR: 0.81, 95% CI: 0.69-0.94), and more pronounced symptoms of depression (OR: 1.08, 95% CI: 1.01-1.15).
Keywords: physical activity; lifestyles; mental health; obesity; medical students